HISTORICAL, RELIGIOUS, AND PHILOSOPHICAL IDEAS OF AHMAD DONISH - Akhmedova, Zebiniso Azizovna (Mental Enlightenment Scientific-Methodological Journal, 2023)
This article analyzes religious studies, where religion was considered a form of social consciousness based on an inadequate, fantastic-illusory reflection of reality. With this approach, a set of immutable dogmas was developed, which function in the same way in different socio-economic and political conditions at all stages of the historical development of society. It is noteworthy that this approach was based on a purely epistemological definition of the early forms of religions, without taking into account the content and essence of the developed monotheistic religions. Yet even primitive religions, in their generic characteristics, were first of all one of the forms of man's self-consciousness, and their fantasticness and illusory nature were only their accidental characteristics.